2018
DOI: 10.1007/s11207-018-1316-3
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric Observations of the Quiet Sun at 20 and 25 MHz in May 2014

Abstract: Results of solar observations at 20 and 25 MHz by the UTR-2 (Ukrainian T-shaped Radio telescope of the second modification) radio telescope in the interferometric session from 27 May to 2 June 2014 are presented. In such a case the different baselines 225, 450, and 675 m between sections of East-West and North-South arms of the radio telescope UTR-2 were used. On 29 May 2014, strong sporadic radio emission consisting of Type III, a Type II and a Type IV bursts was observed. On other days there was no solar rad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…It was shown that the polar and equatorial sizes of the Sun increased with decreasing of frequency following the power law with indexes -0.27 and -0.26 respectively. In addition, these dependences appeared to be very close to the plasma frequency dependence on the distance in undisturbed corona model by Baumbach-Allen [46]. The effective brightness temperature of the solar thermal radio emission was found to be equal to 5 2 10  K, which is several times smaller in magnitude than the kinetic plasma temperature.…”
Section: S R supporting
confidence: 75%
“…It was shown that the polar and equatorial sizes of the Sun increased with decreasing of frequency following the power law with indexes -0.27 and -0.26 respectively. In addition, these dependences appeared to be very close to the plasma frequency dependence on the distance in undisturbed corona model by Baumbach-Allen [46]. The effective brightness temperature of the solar thermal radio emission was found to be equal to 5 2 10  K, which is several times smaller in magnitude than the kinetic plasma temperature.…”
Section: S R supporting
confidence: 75%
“…Both the E-W and N-S radii are significantly larger than the result of Melnik et al (2018). The trend of radius frequency to high frequency is consistent with Mercier & Chambe (2015) and Sharma & Oberoi (2020).…”
Section: Size Of the Sun In Low Frequencysupporting
confidence: 71%
“…The size measured by this method can ignore extended solar radio emission below the half-power level. The Gaussian fitting method assumes the radio source to have a Gaussian-like flux distribution, and fits it with a Gaussian function in UV visibility (Melnik et al 2018) or image space (Ramesh et al 2006). The size of the radio Sun is thus determined by the FWHM of the fitted Gaussian.…”
Section: Size Of the Sun In Low Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus knowing one of these two parameters we can define another one. From the current state of available observation facilities, such as interferometric observations with UTR-2 radio telescope (Dorovskyy, et al, 2018;Melnik, et al, 2018) or tiedarray imaging realized at LOFAR station (Reid and Kontar, 2017;Gordovskyy et al, 2019) it seems more realistic to define the height of the loop as well as its deviation from the normal direction. This will enable us to yield the temperature of the confined plasma, which is difficult to measure by other means at such heights.…”
Section: Analysis and Discussionmentioning
confidence: 99%